Corporate and Household Debt Distress in Latvia : Strengthening the Incentives for Market-Based Approach to Debt Resolution - Saxegaard, Magnus; Erbenova, Michaela; Liu, Yan. (Washington, D.C. : International Monetary Fund, 2011)
This paper reviews Latvia's efforts to manage the increase in debt distress resulting from the unwinding of the 2000-07 credit boom and spillovers from the global financial crisis. The authorities have designed a strategy that strengthens incentives for marked-based debt resolution by improving the legal framework for credit enforcement, introducing tax incentives for debt write-downs, and strengthening financial sector supervision. These measures have started to yield results, but further steps are needed to speed up bankruptcy procedures and reduce credit enforcement costs. Latvia's experience with market-based debt resolution may provide insights on managing debt distress in other countries with limited fiscal resources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet